2013
DOI: 10.3945/ajcn.112.051664
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled trial of vitamin D supplementation in Parkinson disease

Abstract: Vitamin D3 supplementation may stabilize PD for a short period in patients with FokI TT or CT genotypes without triggering hypercalcemia, although this effect may be nonspecific for PD. This trial was registered at UMIN Clinical Trials Registry as UMIN000001841.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 29 publications
7
138
0
8
Order By: Relevance
“…Deficiency of Vitamin D or loss of VDR is usually associated with risk of several neurodevelopmental disorders to loss of antiproliferative functions, thus the absence of VDR or VitD 3 deprives the neurons of needed signals. The studies of Suzuki et al [39] also corroborated this finding that Vitamin D deficiency is a predisposing factor to increased progression of PD. The findings of this study suggest that the progression of such disease conditions is related to process formation and synaptic denervation.…”
Section: Discussionsupporting
confidence: 75%
“…Deficiency of Vitamin D or loss of VDR is usually associated with risk of several neurodevelopmental disorders to loss of antiproliferative functions, thus the absence of VDR or VitD 3 deprives the neurons of needed signals. The studies of Suzuki et al [39] also corroborated this finding that Vitamin D deficiency is a predisposing factor to increased progression of PD. The findings of this study suggest that the progression of such disease conditions is related to process formation and synaptic denervation.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, there is an overexpression of PARP1 in the substantia nigra of PD patients [281]; increased levels of vitamin D down regulate PARP-1 expression, probably mediated by a diminishment of microglial activation [282]. All these aspects considered, clinical trials on vitamin D supplementation in Parkinson's disease have been carried out [283]. Although some data demonstrated that low levels of vitamin D may influence the speed of the disease [283], the supplementation of vitamin D did not modify the disease outcomes.…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%
“…All these aspects considered, clinical trials on vitamin D supplementation in Parkinson's disease have been carried out [283]. Although some data demonstrated that low levels of vitamin D may influence the speed of the disease [283], the supplementation of vitamin D did not modify the disease outcomes. That conclusion probably lies on clinical time of supplementation, far from the initial ones of labs models.…”
Section: Vitamin D Deficiency and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Supplementation with vitamin D is shown to be beneficial in slowing disease progression in animal and cell culture models of PD, [23]. A recent study showed that vitamin D3 supplements stabilized motor symptoms among PD patients [24]. However, it is not clear if a reduction in vitamin D due to nutritional deficiency causes an increase in PD and/or if UV radiation or exposure to sunlight plays a role.…”
Section: Neuroprotective Nutrients Vitaminsmentioning
confidence: 99%